ASSESSMENT OF THE STATE OF EMOTIONAL BURNOUT OF SECONDARY SCHOOL TEACHERS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Emotional exhaustion is a syndrome that occurs as a result of chronic stress in the workplace, especially among professionals working in the educational system. High school teachers are exposed to significant emotional and mental stress, which can lead to occupational exhaustion. This process negatively affects not only the teachers themselves, but also the quality of the educational process.